2016
DOI: 10.3892/ijo.2016.3659
|View full text |Cite
|
Sign up to set email alerts
|

miR-449 overexpression inhibits papillary thyroid carcinoma cell growth by targeting RET kinase-β-catenin signaling pathway

Abstract: Papillary thyroid carcinoma (PTC) is the most common thyroid cancer and represent approximately 80% of all thyroid cancers. The present study is aimed to investigate the role of microRNA (miR)-449 in the progression of PTC. Our results revealed that miR-449 was underexpressed in the collected PTC specimens compared with non-cancerous PTC tissues. Overexpression of miR-449 induced a cell cycle arrest at G0/G1 phase and inhibited PTC cell growth in vitro. Further studies revealed that RET proto-oncogene (RET) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 34 publications
5
13
0
Order By: Relevance
“…Gli2 is the key mediator of Hh-signaling pathway, which is highly conserved in embryonic development, whereas its activation is involved in glioma, BCCs, medulloblastomas, and rhabdomyosarcoma (Boehme et al, 2016;Danhof, Lewis, & Brown, 2017;Raducu et al, 2016;Xu et al, 2017 as our previous study showed (Z. Li et al, 2016). In line with our suspicions, here we found that Gli2 gene knockdown reduces the levels of molecules implicated in the Wnt/β-catenin pathway.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Gli2 is the key mediator of Hh-signaling pathway, which is highly conserved in embryonic development, whereas its activation is involved in glioma, BCCs, medulloblastomas, and rhabdomyosarcoma (Boehme et al, 2016;Danhof, Lewis, & Brown, 2017;Raducu et al, 2016;Xu et al, 2017 as our previous study showed (Z. Li et al, 2016). In line with our suspicions, here we found that Gli2 gene knockdown reduces the levels of molecules implicated in the Wnt/β-catenin pathway.…”
Section: Discussionsupporting
confidence: 90%
“…EpiQuik Nuclear Extraction Kit(EpiGentek, Brooklyn, NY).Western blot analysis was performed as previously described(Z. Li et al, 2016). The FOXE1, Gli2, PCNA, Ki-67, Wnt5a, and β-catenin proteins were detected by using anti-FOXE1 (ab134129; Abcam), anti-Gli2 (ab167389; Abcam), anti-PCNA (ab18197; Abcam), anti-Ki-67 (ab15580; Abcam), anti-Wnt5a (ad72583; Abcam), and anti-β-catenin (ab16051; Abcam) polyclonal antibodies, respectively.…”
mentioning
confidence: 99%
“…Papillary thyroid carcinoma (PTC) is the most common thyroid carcinoma, accounting for approximately 80% of all thyroid malignant tumors (1)(2)(3)(4). Despite highly curable and presenting a 10-year survival rate more than 90%, lymph node metastasis, especially in the neck, occurs in 20-50% of all tumor patients and regional recurrence is found in 5-20% of patients who have undergone total thyroidectomy (3,5,6).…”
Section: Introductionmentioning
confidence: 99%
“…For example, miR-449 shows atypical levels in many cancer types with variations between different tumors. miR-449 plays an important role in gynecological clear cell carcinoma (14), hepatocellular cancer (15), papillary thyroid carcinoma (16) and breast cancer (17). Despite this evidence, the mechanism of action in NSCLC remains to be established.…”
Section: Introductionmentioning
confidence: 99%